Graft Immune Cell Composition Associates with Clinical Outcome of Allogeneic Hematopoietic Stem Cell Transplantation in Patients with AML - Impola, Ulla; Larjo, Antti; Salmenniemi, Urpu; Putkonen, Mervi; Itälä-Remes, Maija; Partanen, Jukka (Frontiers in Immunology, 2016)
Complications of allogeneic hematopoietic stem cell transplantation (HSCT) have been attributed to immune cells transferred into the patient with the graft. However, a detailed immune cell composition of the graft is usually not evaluated. In the present study, we determined the level of variation in the composition of immune cells between clinical HSCT grafts and whether this variation is associated with clinical outcome. Sizes of major immune cell populations in 50 clinical grafts from a single HSCT Centre were analyzed using flow cytometry. A statistical comparison between cell levels and clinical outcomes of HSCT was performed. Overall survival, acute (aGVHD), chronic graft versus host disease (cGVHD), and relapse were used as the primary endpoints. Individual HSCT grafts showed considerable variation in their numbers of immune cell populations, including CD123+ dendritic cells and CD34+ cells, which may play a role in GVHD. Acute myeloid leukemia (AML) patients who developed aGVHD were transplanted with higher levels of effector CD3+ T-, CD19+ B- and CD123+ dendritic cells than AML patients without aGVHD, whereas grafts with a high CD34+ content protected against aGVHD. AML patients with cGVHD had received grafts with a lower level of monocytes and a higher level of CD34+ cells than those without cGVHD. There is considerable variation in the levels of immune cell populations between HSCT grafts and this variation is associated with outcomes of HSCT in AML patients. A detailed analysis of the immune cell content of the graft can be used in risk assessment of HSCT